LIFECYCLE CHALLENGE: MENINGKATKAN KETERAMPILAN KOMUNIKASI BERBASIS GAME EDUKASI DALAM PEMBELAJARAN IPAS KELAS IV - Asa Qolbyatin, Nur; Julianto; Ceffiriana, Paramita; Sunariyah; Hidayati, Fitria (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to improve the communication skills of class IV students in Natural and Social Sciences (IPAS) subjects using the educational game